2020
DOI: 10.21203/rs.3.rs-35598/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy, safety, and long-term survival of concomitant valve replacement and bipolar radiofrequency ablation in patients aged 70 years and older: A comparative study with propensity score matching from a single-centre

Abstract: Background Concomitant bipolar radiofrequency ablation and valve replacement in the elderly remains controversial. In the current study, we aimed to compare the outcomes of concomitant valve replacement and bipolar radiofrequency ablation with valve replacement alone in elderly patients with atrial fibrillation (AF). Methods This was a retrospective study of patients aged ≥ 70 years who underwent valve replacement with or without bipolar radiofrequency ablation in a single-centre between January 2006 and March… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Nakamura et al reported that the rate of freedom from AF in 143 patients (age 65 years or older) with concomitant surgical ablation was 74.9% [18]. The question of whether to perform BRFA in older patients with valvular disease combined with AF simultaneously has been previously explored in several studies [7][8][9][10], including one of our own [14], and some well-known risk factors, such as age, body mass index, and left atrial size, have been shown to adversely affect patients undergoing heart valve surgery combined with AF ablation [19][20][21]. However, to our knowledge, comparative clinical data on risk stratification using a frailty index in older patients undergoing surgical radiofrequency ablation techniques for concurrent AF are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamura et al reported that the rate of freedom from AF in 143 patients (age 65 years or older) with concomitant surgical ablation was 74.9% [18]. The question of whether to perform BRFA in older patients with valvular disease combined with AF simultaneously has been previously explored in several studies [7][8][9][10], including one of our own [14], and some well-known risk factors, such as age, body mass index, and left atrial size, have been shown to adversely affect patients undergoing heart valve surgery combined with AF ablation [19][20][21]. However, to our knowledge, comparative clinical data on risk stratification using a frailty index in older patients undergoing surgical radiofrequency ablation techniques for concurrent AF are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…VR with concomitant BRFA was initially performed under general anesthesia with hypothermic cardiopulmonary bypass through a median sternotomy. The surgical technique details and postoperative treatment (anti-arrhythmic therapy, control of ventricular rate, and anticoagulation) have been described in our previous paper [14]. The Medtronic Cardioblate G2 Surgical Ablation System (Medtronic Inc., Minneapolis, MN) with a bipolar radiofrequency clamp was used for surgical ablation.…”
Section: Surgical Procedures and Postsurgical Treatmentmentioning
confidence: 99%
“…[10] including one of our own, [13] and some well-known risk factors, such as age, body mass index, and left atrial size, have been shown to adversely affect patients undergoing heart valve surgery combined with AF ablation; [17] , [18] , [19] however, to our knowledge, comparative clinical data on risk strati cation using a frailty index in elderly patients undergoing surgical radiofrequency ablation techniques for concurrent AF are lacking. Surgeons often refuse to perform concomitant BRFA because of the patient's frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique details and postoperative treatment (Anti-arrhythmia, control ventricular rate and anticoagulation) has been described in our previous paper. [13] The Medtronic Cardioblate G2 Surgical Ablation System (Medtronic Inc., Minneapolis, MN) with a bipolar radiofrequency clamp was used for surgical ablation. After surgical procedures, patients were admitted to the ICU for early monitoring before being transferred to the general cardiology ward.…”
Section: Surgical Procedures and Postsurgical Treatmentmentioning
confidence: 99%